2007
DOI: 10.1095/biolreprod.106.056028
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Sperm Surface Thiols Modulates Adhesion to the Fallopian Tube Epithelium1

Abstract: Sperm that adhere to the fallopian tube epithelium are of superior quality and adhesion extends their fertile life. It has been postulated that periovulatory signals, as yet undefined, promote sperm release. In the in vitro studies described here, we examined the effects of several antioxidants, reportedly present within oviductal fluid, on the modulation of sperm-oviduct adhesion in bovine species. Results showed that 1) the cell-permeant thiols (penicillamine, beta mercaptoethanol, cysteine, and dithiotreito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 48 publications
5
38
0
Order By: Relevance
“…However, in the present study, we observed that AEA has no effects on sperm-oviduct binding and sperm release, even at a concentration of 5 mM. These data are in agreement with several evidences showing that release of spermatozoa bound to the oviductal reservoir is promoted by capacitation (Lefebvre & Suarez 1996, Gualtieri et al 2005, Talevi et al 2007, Talevi & Gualtieri 2010, whereas AEA has been shown to depress this process, at least in human and boar (Rossato et al 2005, Maccarrone et al 2005. Herein, sperm-ZP binding experiments demonstrated that AEA depresses sperm capacitation also in the bovine species.…”
Section: Sperm-oviduct Interactionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, in the present study, we observed that AEA has no effects on sperm-oviduct binding and sperm release, even at a concentration of 5 mM. These data are in agreement with several evidences showing that release of spermatozoa bound to the oviductal reservoir is promoted by capacitation (Lefebvre & Suarez 1996, Gualtieri et al 2005, Talevi et al 2007, Talevi & Gualtieri 2010, whereas AEA has been shown to depress this process, at least in human and boar (Rossato et al 2005, Maccarrone et al 2005. Herein, sperm-ZP binding experiments demonstrated that AEA depresses sperm capacitation also in the bovine species.…”
Section: Sperm-oviduct Interactionsupporting
confidence: 93%
“…2). Bovine spermatozoa can be released in vitro from oviductal monolayers by heparin and penicillamine, which have been previously validated as powerful inducers of sperm release (Talevi & Gualtieri 2001, Talevi et al 2007. Spermatozoa released by penicillamine had the same CB1 immunolocalization observed in the initial sperm population (compare Figs 1a and 3a).…”
Section: Immunolocalization Of Cb1 and Cb2 In Bovine Spermatozoamentioning
confidence: 54%
See 2 more Smart Citations
“…PEN, and other thiols (compounds with a sulfhydryl group), have been shown to initiate sperm release through the reduction of sperm surface disulfides to sulfhydryls (Talevi et al 2007, Gualtieri et al 2009. It is probable that PEN may prevent or revert sperm association by the reduction of disulphide bonds of a sperm protein, which are required for sperm binding, to free sulfhydryls.…”
Section: Discussionmentioning
confidence: 99%